2020
DOI: 10.1093/nar/gkaa544
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive nucleosome interactome screen establishes fundamental principles of nucleosome binding

Abstract: Abstract Nuclear proteins bind chromatin to execute and regulate genome-templated processes. While studies of individual nucleosome interactions have suggested that an acidic patch on the nucleosome disk may be a common site for recruitment to chromatin, the pervasiveness of acidic patch binding and whether other nucleosome binding hot-spots exist remain unclear. Here, we use nucleosome affinity proteomics with a library of nucleosomes that disrupts all exposed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 83 publications
1
62
0
Order By: Relevance
“…Indeed, it has been shown for PHD1/2 readers that they can bind up to ten-fold tighter to histone peptides compared to free nucleosomes [19]. A recent large-scale experimental study also demonstrates that many chromatin factors show enhanced binding to tailless nucleosomes compared to the full nucleosome, resulting from the increased solvent accessibility of DNA [57]. Our estimates of the binding free energy of the histone tail binding to DNA based on conformational sampling are on the order of several kcal/mol for H3 and H4 tails with the strongest binding exhibiting for H3 tail (Table SM4), which is consistent with previous experimental data on the tail-DNA binding free energies [58].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown for PHD1/2 readers that they can bind up to ten-fold tighter to histone peptides compared to free nucleosomes [19]. A recent large-scale experimental study also demonstrates that many chromatin factors show enhanced binding to tailless nucleosomes compared to the full nucleosome, resulting from the increased solvent accessibility of DNA [57]. Our estimates of the binding free energy of the histone tail binding to DNA based on conformational sampling are on the order of several kcal/mol for H3 and H4 tails with the strongest binding exhibiting for H3 tail (Table SM4), which is consistent with previous experimental data on the tail-DNA binding free energies [58].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown that the C-terminal domain of Elys, including the AT-hook, directly binds nucleosomes and H2A/H2B histone dimers [ 91 , 92 ]. This binding occurs with the acidic patch of H2A/H2B dimers [ 93 , 94 ].…”
Section: Genome-wide Interactions Of Elys and Other Nupsmentioning
confidence: 99%
“…Out data suggest that binding of the linker region through the arginine anchors to the H2A-H2B acidic pocket of the nucleosome stabilizes the activated conformation and/or prevents the enzyme from zipping back to the autoinhibited state, providing the mechanisms of ALC1 regulation by the nucleosomal epitopes. The residues neighboring the H2A-H2B acidic pocket are subjected to modifications, and the acidic pocket is believed to function as a tunable hub for many chromatin proteins 11,30 . Several chromatin remodelers, including Snf2 and ISWI, are also regulated by the H2A-H2B acidic pocket, although the mechanisms are not completely clear [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%